Routine vaccination coverage of children aged 1-7 years in Zhejiang province, China - Yu Hu; Yaping Chen; Hui Liang; Ying Wang (Taylor & Francis Group, 2018)
Background: This study was to evaluate the coverage, completeness and timeliness of routine vaccination among children aged 1-7 years in Zhejiang province. Methods: Demographic information and immunization records of 4613160 children born from Jan 1, 2010 to Dec 31, 2016 were extracted from Zhejiang provincial immunization information system (ZJIIS) on Dec 31, 2017. Vaccination coverage for each vaccine dose and completeness of different vaccine series were calculated by birth cohort, immigration status, and geographic area. The timeliness of vaccine doses scheduled before 12 months of age for the 2016 birth cohort was also examined Results: Coverage of all the vaccine doses scheduled before 12 months of age and its completeness reached the target goal of 90%. The coverage and completeness decreased substantially in vaccinations scheduled after 12 months old, and most of them were below 90%. The coverage and timeliness estimates of migrant children was lower than those of resident children and the coverage of WenZhou (WZ), Zhoushan (ZS) and Lishui (LS) was lower than other cities across all the birth cohorts. Despite high coverage rates for all antigens by age 12 months, there was a very large range of percent of vaccination delay when comparing different antigens scheduled in the first year of life for the 2016 birth cohort. Conclusions: This study demonstrated the success and improvement of immunization program in Zhejiang province, and identified some challenges. Strategies such as assessment, feedback, incentives, and exchange program, reminder/recall activity, home visits, immunization requirement for school's enrollment could be used to reach a higher coverage of the population.